2015
DOI: 10.3992/jgb.10.3.87
|View full text |Cite
|
Sign up to set email alerts
|

Novel Integrated Design Strategies for Net-Zero-Energy Solar Buildings (Nzesbs) in Nanjing, China

Abstract: The connotations and denotations of the term net-zero-energy solar buildings (NZESBs) have been in constant flux because of continuous developments in solar heating technology, solar photovoltaic (PV) technology, building energy-storage technology, regional energy-storage technology, and energy-management systems. This paper focuses on innovative strategies for implementing NZESBs in Nanjing, China. These strategies include integrated architectural design, including passive solar design (respecting climatic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…These experiences normally include several meetings and the use of evaluations tools, along with changes in design attributes and the incorporation of special building products and systems. Recently, similar initiatives have demonstrated that it is possible to achieve near-zero building design (Attia et al , 2015; Peng et al , 2015; Azarbayjani et al , 2014) with the use of solar collection technologies and passive strategies. Additionally, experiences in professional education with multidisciplinary teams (Vassigh and Spiegelhalter, 2014) and collaborative exhibits (Todd and Lindsey, 2016), as well as using advanced computational analysis (O’Brien et al , 2013) and diverse building systems (Baudains et al , 2014) have shown relevant achievements in the integrated design process.…”
Section: Methodsmentioning
confidence: 99%
“…These experiences normally include several meetings and the use of evaluations tools, along with changes in design attributes and the incorporation of special building products and systems. Recently, similar initiatives have demonstrated that it is possible to achieve near-zero building design (Attia et al , 2015; Peng et al , 2015; Azarbayjani et al , 2014) with the use of solar collection technologies and passive strategies. Additionally, experiences in professional education with multidisciplinary teams (Vassigh and Spiegelhalter, 2014) and collaborative exhibits (Todd and Lindsey, 2016), as well as using advanced computational analysis (O’Brien et al , 2013) and diverse building systems (Baudains et al , 2014) have shown relevant achievements in the integrated design process.…”
Section: Methodsmentioning
confidence: 99%
“…Insulation is recognized as one of the most vital parameters of energy conservation in buildings. In recognition of this importance, all energy regulations for buildings judge efficiency using the Heat Transfer Coefficient (U-value) of a building envelope, including the external walls, roof, and windows [17]. The main objective of the U-value is to measure heat transfer through the envelope, where a smaller U-value indicates better insulation [18].…”
Section: Introductionmentioning
confidence: 99%